2016
DOI: 10.1080/10255842.2016.1268132
|View full text |Cite
|
Sign up to set email alerts
|

A case for poroelasticity in skeletal muscle finite element analysis: experiment and modeling

Abstract: Finite element models of skeletal muscle typically ignore the biphasic nature of the tissue, associating any time dependence with a viscoelastic formulation. In this study, direct experimental measurement of permeability was conducted as a function of specimen orientation and strain. A finite element model was developed to identify how various permeability formulations affect compressive response of the tissue. Experimental and modeling results suggest the assumption of a constant, isotropic permeability is ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Our model further supports experimental findings of increases in fluid pressure with passive muscle tension [4]. In fact, some studies have suggested that fluid content in muscle may play a role in passive stiffness either through poroelasticity [21,55] or modeling muscle fibers as volumes filled with incompressible fluid [56,57]. However, the length dependency of fluid pressure in our model under contractile conditions suggests that variability of intramuscular pressure in vivo may be dependent on other physiological conditions (in this case muscle length) in addition to muscle force.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our model further supports experimental findings of increases in fluid pressure with passive muscle tension [4]. In fact, some studies have suggested that fluid content in muscle may play a role in passive stiffness either through poroelasticity [21,55] or modeling muscle fibers as volumes filled with incompressible fluid [56,57]. However, the length dependency of fluid pressure in our model under contractile conditions suggests that variability of intramuscular pressure in vivo may be dependent on other physiological conditions (in this case muscle length) in addition to muscle force.…”
Section: Discussionsupporting
confidence: 89%
“…For the current model, the assumption was made that the excitable constituent did not contain a fluid component, and as such the constitutive approaches for the excitable and passive constituents are very similar, with the only exception being that the excitable constituent did not include a permeability/poroelasticity. Thus, it is assumed that the excitable tissue is comprised of solid material only as a compressible hyperviscoelastic material [17][18][19][20], while passive tissue was modeled as compressible hypervisco-poroelastic material [21].…”
Section: Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Facial muscles have been modeled in a more complex manner using a fiber-based and orthogonal direction-based elastic material [24] or a nonlinear elastic-viscoplastic model [21] or an orthogonal elastic material [25] or a hyperelastic material using the Mooney-Rivlin formulation [26]. Moreover, skeletal muscles in the upper limbs (subscapularis, supra, and infraspinatus), spine, and lower limbs (ischios, quadriceps, gracilis, sartorius, gastrocnemius, and biceps femoris) have been commonly modeled using a hyperelastic material [27] (based on the Neo-Hookean formulation [2830] or based on the Mooney-Rivlin formulation [26, 31, 32]) or a nonlinear viscoelastic material [33] or a visco-poroelastic material [34]. In fact, the use of hyperelastic models assumes that the skeletal muscle exhibits a large deformation (>5%) behavior under external solicitation while visco-poroelastic law allows the fluid-filled fiber fascicles and connective tissue to be taken into consideration in model formulation.…”
Section: Continuum Models Of Skeletal Musclesmentioning
confidence: 99%
“…Note that the number of model parameters increases when more biophysical phenomena are included into constitutive laws. For example, three main parameters are required to formulate the visco-poroelastic material [34]. Six parameters are needed to define the nonlinear elastic-viscoplastic model [21].…”
Section: Continuum Models Of Skeletal Musclesmentioning
confidence: 99%